PENERAPAN MODEL CHILDREN’S LEARNING IN SCIENCE BERBANTUAN MEDIA AUDIO VISUAL (SOUND SLIDE) UNTUK MENINGKATKAN HASIL BELAJAR IPAS KELAS V SD ISLAM TERPADU ISLAM NURUL SINGKAWANG - Nurrahma, Mulia; Evinna Cinda Hendriana; Abd Basith (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to 1) determine the improvement of student learning outcomes through the implementation of the CLIS model assisted by audio visual media (sound slide) at SD-IT Nurul Islam Singkawang; 2) to determine student responses after the implementation of the CLIS model assisted by audio visual media (sound slide) at SD-IT Nurul Islam Singkawang. The type of research used is quantitative with a one group pre-test post-test research design. The population in this study were all grade V students of SD-IT Nurul Islam Singkawang and the sample in this study used a total sampling of the entire class V Hud as many as 27 students. The results of the study showed that 1) Hypothesis testing using the Wilcoxon test obtained a sig value of 0.001 (0.001 <0.05), so it can be concluded that there is an increase in the learning outcomes of class V Hud students after the application of the CLIS learning model assisted by audio-visual media (sound slides) in the science subject of SD-IT Nurul Islam Singkawang students.; 2) Based on the results of the calculation of the student response questionnaire showed an average of 75%, it can be concluded that the implications of this study indicate that the application of the CLIS model assisted by audio-visual media (sound slides) can have a positive impact on student learning outcomes, especially on magnet material and its uses. Keywords: CLIS model, assisted by audio-visual media (sound slides), learning outcomes.